2018
DOI: 10.1021/acsomega.8b02817
|View full text |Cite
|
Sign up to set email alerts
|

Sol–Gel Synthesis of Ce4–xSr1+xFe5–xZnxO14+δ [0 ≤ x ≤ 0.45] Superparamagnetic Oxide Systems and Its Magnetic, Dielectric, and Drug Delivery Properties

Abstract: In this work, we have successfully synthesized superparamagnetic nanocomposites, Ce 4– x Sr 1+ x Fe 5– x Zn x O 14+δ (0 ≤ x ≤ 0.45) (CSFZ) (TA1–TA4: x = 0, 0.15, 0.30, and 0.45) via the Nitrate–citrate sol–gel method. X-ray diffraction studies show the formation of single-phase nanocomposites (NCs) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…It was reported that the nanoparticles have the potential for being used as drug delivery systems as well as bioactive fillers for various applications such as wound healing and bone regeneration. Thangaraj et al [180] synthesized superparamagnetic Ce 4 −xSr 1+x Fe 5−x ZnxO 14+δ (x=0-0.45) nanocomposites by the nitrate-citrate sol-gel route for different applications such as drug delivery, sensor, dielectric, conductivity studies, and optical properties. Pathania et al [181] studied the drug release kinetics of chitosan-g-poly(acrylamide)/ Zn (CPA-Zn) nanocomposite synthesized by microwave radiations.…”
Section: The State-of-the-art Of Composites Containing Zn and Mg In Dmentioning
confidence: 99%
“…It was reported that the nanoparticles have the potential for being used as drug delivery systems as well as bioactive fillers for various applications such as wound healing and bone regeneration. Thangaraj et al [180] synthesized superparamagnetic Ce 4 −xSr 1+x Fe 5−x ZnxO 14+δ (x=0-0.45) nanocomposites by the nitrate-citrate sol-gel route for different applications such as drug delivery, sensor, dielectric, conductivity studies, and optical properties. Pathania et al [181] studied the drug release kinetics of chitosan-g-poly(acrylamide)/ Zn (CPA-Zn) nanocomposite synthesized by microwave radiations.…”
Section: The State-of-the-art Of Composites Containing Zn and Mg In Dmentioning
confidence: 99%